Penguatan Pendidikan Politik Berbasis Syariat Islam dalam Konteks Sistem Demokrasi di Aceh - Fitri, Maulidar; Suhendra, Dede (Jurnal Ilmiah Guru Madrasah, 2025)
Aceh is the only province in Indonesia that officially implements Islamic Sharia within its governmental system, including in the realm of political education. In a democratic context, integrating Islamic Sharia values with modern political systems presents both challenges and opportunities. Political education grounded in Islamic values is essential for enhancing public political awareness without contradicting democratic principles. This study aims to explore how Islamic Sharia-based political education can be strengthened within Aceh’s democratic system. The research employs a library research method with a descriptive qualitative approach, analyzing literature, legal documents, and academic studies related to Sharia, democracy, and political education in Aceh. The findings show that strengthening political education in Aceh based on Islamic Sharia can be implemented through formal education curricula, community outreach, and the empowerment of Islamic institutions such as the Ulama Consultative Assembly (MPU) and the Sharia Office. This integration not only reinforces Aceh’s Islamic identity but also deepens democratic understanding aligned with local values.